Effect of caffeine in chocolate (Theobroma cacao) on the alveolar bone mineral density in guinea pigs (Cavia cobaya) with orthodontic tooth movement - Bramita Beta Arnanda; Sri Suparwitri; Pinandi Sri Pudyani (Dental Journal (Majalah Kedokteran Gigi), 2020)
Background: The benefits of chocolate have attracted significant attention from clinicians, especially the active compound of caffeine on bone metabolism. The bone density significantly affected the rate of tooth movement. Purpose: This study aims to analyse the effect of the dose and the duration of caffeine consumption in chocolate on alveolar bone mineral density in orthodontic tooth movement. Methods: Forty-eight male guinea pigs (Cavia cobaya) aged between 3-4 months and weighing 300-350 grams were divided into four groups (group A control, group B caffeine dose of 2.3 mg, group C caffeine dose of 3.45 mg, and group D caffeine dose of 4.6 mg). An open coil spring was applied to the mandibular inter-incisor with an orthodontic force of 35 grams. Guinea pigs were sacrificed using lethal doses of anaesthetics on days 0, 1, 7, and 14 after an orthodontic appliance installation. Mandibular alveolar bone mineral density in compression sites was analysed with an atomic absorption spectrophotometer (AAS). Experiment data results were analysed using two-way ANOVA with a 95% degree of confidence. Results: Caffeine consumption with a dose of 4.6 mg on day 7 had the lowest alveolar bone mineral density and the highest was at a dose of 2.3 mg on day 14, but there were no differences between the dose groups, the duration groups and interactions between both of them (p>0.05). Conclusion: The consumption of caffeine in chocolate did not decrease the bone mineral density in the compression site of orthodontic tooth movement.